NEW INTERNATIONAL ILLUSTRATED ENCYCLOPEDIA OF ART - Rothenstein, John (edición) (1967)
CONTENIDO: V. 1 AACHEN - ARCHITECTURAL TERMS. -- V. 2 ARCHITECTURAL TERMS - BAROQUE ART AND ARCHITECTURE. -- V. 3 BAROQUE ART AND ARCHITECTURE - BRAQUE. -- V. 4 BRASILIA - CARIANI. -- V. 5 CARICATURE AND CARTOON - CINQUECENTO. -- V. 6 CIRCUS - DE HOOCH. -- V. 7 DEINEKA - EMBROIDERY. -- V. 8 EMERALD - FRENCH ART AND ARCHITECTURE. -- V. 9 FRENCH ART ANDARCHITECTURE - GIOTTO. -- V. 10 GIOVANNI D'ALEMAGNA - HALS. -- V. 11 HAMEN - INGRES. -- V. 12 INMAN - LE CLERC FAMILY. -- V. 13 LE CORBUSIER - MASOLINO. -- V. 14 MASON'S MARKS - NEO-ROMANTICISM. -- V. 15 NEPALESE ART - PHILOXENOS. -- V. 16 PHOENICIAN ART AND ARCHITECTURE - PRAXITELES. -- V. 17PRE-COLUMBIAN ART AND ARCHITECTURE - RILEY, BRIDGET. -- V.18 RILEY, JOHN - RYSSELBERGHE. -- V. 19 SAARINEN FAMILY - SOUTH PACIFIC ART AND ARCHITECTURE. -- V. 20 SOUTHEAST ASIAN ART AND ARCHITECTURE - TEN, THE. -- V. 21 TENEBRISM - UNITED STATES ART AND ARCHITECTURE. -- V. 22 UNITED STATES ARTAND ARCHITECTURE - VATICAN, THE. -- V. 23 VAULT - WHITTREDGE. -- V. 24 WILDENS - INDEX